Variants of cognitive deficiency depending on the clinical characteristics of the disease in patients with paranoid schizophrenia - G. G. Lebedeva; E. R. Isaeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Pecific aspects of cognitive impairments in patients with paranoid schizophrenia depending on the clinical characteristics of the disease have been studied. One hundred and thirty patients were examined. A clinico-psychological, experimental psychological and statistical methods were used. Three main types of cognitive deficiency with paranoid schizophrenia, associated with the onset, disease duration, and severity of psychiatric symptomology : 1) long-term course of the disease accompanied by the average level of clinical symptomology associated with abnormal attention and visuospatial functions; 2) late onset of the disease and unexpressed clinical symptomology combined with memory impairments; 3) acute onset and early age combined with the absence of cognitive impairments.